Unconventional machining method for enhancing the durability of tools and strength of the specimens bonded - Makedonski, Aleksandar (Manufacturing Technology Journal, 2011)
The article presents the results from the application of a new method for raising the exploitation characteristics of metal-cutting tools, which includes preliminary combined magnetic field and ultrasound processing of the instrument. The indirect effect of the processing on the cutting force as well as on the roughness of the processed surface and on the wearing of the instruments during the drilling and milling processes has been studied. Demonstrated the effectiveness of the method on shear strength of the metal samples bonded
Keywords: magnetic-ultrasound; wear-resistance; dependent variables; shear strength